Effectiveness of screening for diabetic retinopathy by nonspecialist doctors: the importance of physician-ophthalmologist collaboration in the prevention of blindness. Sri Lanka Young Diabetes Study (SLYDS) - Wijesinghe, N.P.; Jayaweera, M.; Wijetunga, W.M.U.A.; Dissanayake, H.A.; Matthews, D.R.; Pathirana, S.; Katulanda, P. (Sri Lanka College of Endocrinologists, 2014)
Introduction: Diabetes retinopathy (DR) is the fourth leading cause for blindness worldwide. Screening is vital for its early detection and prevention of blindness. However screening all diabetic patients by specialists is impossible, particularly in resource poor settings such as Sri Lanka. We aimed to compare the agreement between non-specialist doctors and specialist ophthalmologists in diagnosing DR and planning follow up. Methods: A descriptive study was conducted with a cohort of patients randomly recruited from the Sri Lanka Young Diabetes Study (SLYDS). They were examined by a group of non-specialist doctors by direct ophthalmoscopy after mydriasis, and specialists (by slit lamp biomicroscopy) who were blinded to non-specialist doctors’ finding. Agreement between DR grading according to International Clinical Diabetic Retinopathy Disease Severity Scale, and follow up decisions, by non-specialist and specialist doctors were assessed with kappa statistic, using SPSS-16. Results: Our study included 658 participants (males 36%, mean age 37.1 years, mean duration of diabetes 5.22 years (± 4.04), mean HbA1c 8.1% (±2.04)) and 123 (18.7%) had diabetes retinopathy and 54 (8.3%) required early referral. Exact agreement between ophthalmologists and non specialist doctors in determining absence or presence of diabetes retinopathy was 0.82 (Kappa 0.48, p < 0.001) while the agreement in diagnosing the grade of retinopathy was 0.76 (Kappa 0.347, p < 0.001). Junior doctors detected DR with a sensitivity and specificity of 0.68 and 0.86 respectively. Exact agreement on follow up decision was 0.92 (Kappa 0.48, p < 0.001), with 0.52 sensitivity and 0.96 specificity in decision for early referral. Conclusion: Non-specialist doctors can identify DR with reasonable sensitivity. This should be encouraged in primary care, particularly in resource poor settings. Referring patients with any form of DR to a specialist should be recommended to prevent those with severe degrees of retinopathy from being missed for appropriate specialist care.
Keywords: diabetes retinopathy; blindness; prevention; screening; non-specialist doctors